FAKTOR - FAKTOR YANG MEMPENGARUHI IBU DALAM PEMBERIAN ASI EKSKLUSIF PADA BAYI DI DESA PAL IV PIJORKOLING KECAMATAN PADANGSIDIMPUAN TENGGARA TAHUN 2016 - Pohan, Rostina Afrida; Hidayah, Arinil . (Jurnal Kesehatan Ilmiah Aufa Royhan, 2016)
Exclusive breastfeeding is breastfeeding without other additional food and drink in infants aged 0-6 months. Food and other beverages in question, for example water, milk, formula, juice, honey, tea, or solid foods such as banana, papaya, milk porridge, biscuits, rice porridge, and the team. The purpose of this study was to determine the factors that influence mothers in exclusive breastfeeding in the village Pal IV Pijorkoling District of Southeast Padangsidimpuan 2016. The design used in this research is descriptive correlation whit a sampling technique is done in total sampling rate of 49 people. Debgen data collection is done using a questionaire. The study was conducted in January 2016 to August 2016. The results showed no effect between jobs p = 0.005 ( p <0.05 ), p = 0.001 Resources ( p <0.05 ), and family support p = 0.002 ( p <0,05 ) to exclusive breastfeeding. Expected cadres or health officials to pay more attention to the factors that influence mothers in exclusive breastfeeding, and prepare expectant mothers for later after giving birth can give exclusive breastfeeding and involve families in the success of the provision of exclusive breastfeeding to their babies so that factors during this influence in pemberikan Exclusive breastfeeding mothers do not affect a mother again.